Absorption Refrigeration Systems Based on Ammonia as Refrigerant Using Different Absorbents: Review and Applications - Alvaro A. S. Lima; Gustavo de N. P. Leite; Alvaro A. V. Ochoa; Carlos A. C. dos Santos; José A. P. da Costa; Paula S. A. Michima; Allysson M. A. Caldas (Energies, 2020)
The interest in employing absorption refrigeration systems is usually related to electricity’s precariousness since these systems generally use thermal rejects for their activation. The application of these systems is closely linked to the concept of energy polygeneration, in which the energy demand to operate them is reduced, which represents their main advantage over the conventional vapor compression system. Currently, the solution pairs used in commercial absorption chillers are lithium bromide/water and ammonia/water. The latter pair has been used in air conditioning and industrial processes due to the ammonia operation’s low temperature. Few review papers on absorption chillers have been published, discussing the use of solar energy as the input source of the systems, the evolution of the absorption refrigeration cycles over the last decades, and promising alternatives to increase the performance of absorption refrigeration systems. There is a lack of consistent studies about designing requirements for absorption chillers, so an updated review covering recent advances and suggested solutions to improve the use and operation of those absorption refrigeration systems using different working fluids is relevant. Hence, this presents a review of the state-of-the-art of ammonia/absorbent based absorption refrigeration systems, considering the most relevant studies, describing the development of this equipment over the years. The most relevant studies in the open literature were collected to describe this equipment’s development over the years, including thermodynamic properties, commercial manufacturers, experimental and numerical studies, and the prototypes designed and tested in this area. The manuscript focuses on reviewing studies in absorption refrigeration systems that use ammonia and absorbents, such as water, lithium nitrate, and lithium nitrate plus water. As a horizon to the future, the uses of absorption systems should be rising due to the increasing values of the electricity, and the environmental impact of the synthetic refrigerant fluids used in mechanical refrigeration equipment. In this context, the idea for a new configuration absorption chiller is to be more efficient, pollutant free to the environment, activated by a heat substantiable source, such as solar, with low cost and compactness structure to attend the thermal needs (comfort thermal) for residences, private and public buildings, and even the industrial and health building sector (thermal processes). To conclude, future recommendations are presented to deal with the improvement of the refrigeration absorption chiller by using solar energy, alternative fluids, multiple-effects, and advanced and hybrid configurations to reach the best absorption chiller to attend to the thermal needs of the residential and industrial sector around the world.